Adapting the Multilingual Assessment Instrument for Narratives (MAIN) to Chilean Spanish - Iturra-Osorio, Daniela; Camus Torres, Alondra; Allende-Valenzuela, Tamara; Aparici Aznar, Melina (Revista de Investigación en Logopedia, 2025)
The main objective of this study was to carry out the cross-cultural adaptation of the Multilingual Assessment Instrument for Narratives – MAIN, a narrative assessment instrument available in several languages, to Chilean Spanish. The adaptation process involved six stages: direct translation, synthesis, back-translation, revision and preliminary version, piloting, final report and presentation to the committee of experts. The adaptation paid special attention to lexical, grammatical, and cultural aspects to ensure the comprehension and familiarity of the instrument in the everyday context of Chilean children, without compromising the original structure and format of the test. In line with previous studies in other languages, the results of the pilot test revealed an increase in performance in the narrative production categories with the age of children from 4 to 7 years. Regarding comprehension, an improvement with age was observed, reaching a peak around 6 years of age. These findings are consistent with previous research conducted with the MAIN. The availability of a tool adapted to different languages facilitates the comparison and exchange of data between professionals and researchers from a range of linguistic and cultural contexts. This work also promotes the adaptation of the MAIN to other languages spoken in Ibero-America, opening up the possibility of assessing language combinations that are not usually assessed.
Keywords: Transcultural Adaptation; Assessment; MAIN; Narrative